ENTEROBACTER SAKAZAKII BE INHIBITED BY TRIGONA SPP. PROPOLIS FROM PANDEGLANG INDONESIA - A.E.Z. HASAN,; SURYANI,; S. ESTUNINGSIH,; FITRIANNUR, (International Journal of Pharma and Bio Sciences, 2015)
Propolis has many advantages and specific potencies, due to its properties as antibacterial, antivirus, and anticancer. Aim of the study is to determine the propolis potency of Trigona spp as antibacterial agent against E. sakazakii. The antibacterial activity test was performed by a modified agar well diffusion against three isolates of bacteria E. sakazakii IB-19b, IB-29a, and ATCC 35217. Through the initiation test, propolis activity was higher than commercial propolis, and lower than ampicillin. The effect of propolis extract to commercial propolis for each isolate IB-19b, IB -29a, and ATCC 35217 were 143.99%, 169.65%, and 155.76% respectively. The effects of propolis extract to ampicillin for each isolate IB-19b, IB-29a, and ATCC 35217 were 39.37%, 38.94%, and 47.37% respectively. The minimum inhibition concentration (MIC) differed for each isolate, the minimum inhibition concentration for IB-19b, IB-29a, and ATCC 35217 were 12.50%, 25.00%, and 50.00% respectively.